Performance Evaluation of MQTT Broker Servers Deployed in the Cloud - Pazos, Fernando Agustin (2023)
Communication between devices on a network requires the use of protocols. On internet there are well known protocols that can be used both in the architecture of a server with multiple clients as well as in a machine to machine (M2M) communication. In Internet of Things (IoT) applications, network communication can be supervised by a server denoted as broker, and the most widely used application layer protocol for this purpose is MQTT (Message-Queuing Telemetry Transport). This paper compares the performance of eight publicly available MQTT brokers deployed in the cloud in three experiments under different stress conditions. The goal is to choose the most suitable broker to be used in the communication between a Cubesat-type nanosatellite and the land terminal.